2017
DOI: 10.1007/s11738-017-2523-5
|View full text |Cite
|
Sign up to set email alerts
|

Early trans-plasma membrane responses to Tobacco mosaic virus infection

Abstract: Early trans-plasma membrane behavior after in vivo mechanical inoculation of Nicotiana tabacum with Tobacco mosaic virus (TMV) was investigated and compared to virus quantification in leaf tissues. To identify early events related to virus/host interaction, the systemic virus TMV was used to infect lower leaves and tests were carried out on upper leaves which were not directly infected. Non-invasive microelectrodes were used to estimate trans-plasma membrane electron transport and membrane potential after arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Viral infection is supposed to facilitate the entry of the RIP, which inactivates cell ribosomes, causing cell death and preventing the virus from using the cellular machinery to replicate and spread [125]. So far, the mechanism by which the virus facilitates the entry of RIPs has not been shown, although the ability of viruses to modify plasma membrane permeability is well-known [126]. In the cytosol, it can inactivate ribosomes (rRNA glycosylase activity), causing the death of infected cells and thus preventing the spread of the virus.…”
Section: Antiviral Mechanisms Of Ripsmentioning
confidence: 99%
“…Viral infection is supposed to facilitate the entry of the RIP, which inactivates cell ribosomes, causing cell death and preventing the virus from using the cellular machinery to replicate and spread [125]. So far, the mechanism by which the virus facilitates the entry of RIPs has not been shown, although the ability of viruses to modify plasma membrane permeability is well-known [126]. In the cytosol, it can inactivate ribosomes (rRNA glycosylase activity), causing the death of infected cells and thus preventing the spread of the virus.…”
Section: Antiviral Mechanisms Of Ripsmentioning
confidence: 99%
“…Viral particles were purified from diseased N. tabacum plants form leaves (50g of tissue) (Uhde-Holzem et al, 2010). According to Rettcher et al (2015), polyethylene glycol (PEG) precipitation method was performed as reported by Uhde-Holzem et al (2010) omitting the sucrose cushion centrifugation to limit losses in TMV amount (Luvisi et al, 2017). Following the sucrose gradient step, selected fractions were pooled, followed by centrifugation at 248,000 × g for three hours.…”
Section: Tmv Production Purification and Assaymentioning
confidence: 99%